Procedural meaning problems and perspectives - Escandell-Vidal, Victoria; Leonetti, Manuel; Ahern, Aoife (Bingley, U.K. : Emerald, 2011)
Although the notion of procedural meaning is found in areas such as discourse markers, reference, tense, modality and intonation, until now there has been no single volume entirely devoted to it. Over 25 years, since the initial proposal by Blakemore, a number of refinements have been suggested, yet some criticisms have also been raised. The role and status of the conceptual / procedural distinction within a theory of human communication and the nature of procedural encoding were in need of reassessment in the light of current research in linguistic theory, cognitive science, experimental pragmatics and language acquisition. The papers collected here serve this general purpose from different standpoints. Some of them consider the topic from the angle of its theoretical foundations and put forth original proposals aimed at clarifying the most controversial issues. Others take a more data-driven orientation and offer novel analyses illustrating how encoded instructions work and how much can be gained from approaching certain linguistic phenomena in procedural terms. The contributions in this volume represent an inflection point in the delimitation and understanding of the notion of procedural meaning and open new paths for future research.
1. The conceptual-procedural distinction : past, present and future / Deirdre Wilson -- 2. On the status of procedural meaning in natural language / Carmen Curc-- 3. On some methodological issues in the conceptual/procedural distinction / Louis de Saussure -- 4. On the rigidity of procedural meaning / Victoria Escandell-Vidal, Manuel Leonetti -- 5. Exploring the borderline between procedural encoding and pragmatic inference / Christoph Unger -- 6. Description as indication : the use of conceptual meaning for a procedural purpose / Thorstein Fretheim -- 7. Definiteness, procedural encoding and the limits of accommodation / Christopher Lucas -- 8. Beyond reference : concepts, procedures and referring expressions / Kate Scott -- 9. Child language, theory of mind, and the role of procedural markers in identifying referents of nominal expressions / Jeanette K. Gundel -- 10. Cross-linguistic variation in procedural expressions : semantics and pragmatics / JosAmen{u2BF3}-Pons -- 11. Assertion, relevance and the declarative mood / Mark Jary -- 12. The procedure of marking contrast with alternatives : a constraint in the derivation of higher level explicatures / Susana Olmos, Laura Innocenti, John Saeed -- 13. A procedural analysis of kadhalik / Mai Zaki -- 14. Sentence stress and the procedures of comprehension / Daniel J. Sax -- 15. Procedural encoding and tone choice in Buenos Aires Spanish / Leopoldo O. Labast.
Mode of access: World Wide Web.
Keywords: Language Arts & Disciplines -- Linguistics -- Semantics; Language Arts & Disciplines -- Linguistics -- General; Semantics; Grammar, syntax; Language and languages -- Philosophy